The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2010
DOI: 10.12693/aphyspola.117.786
|View full text |Cite
|
Sign up to set email alerts
|

Nanostructured Materials for Optoelectronic Applications

Abstract: Study and optimization of new nanoscale materials useful for optoelectronic application have been considered. The search for the effective nanostructured materials has been revealed in two directions: to optimize the mechanical hardness of the inorganic systems and to increase the photorefractive parameters of the organics with nanoobjects. It has been testified that the surface mechanical properties of the inorganic materials via nanotubes treatment process can be drastically improved. For example, the surfac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 13 publications
(5 citation statements)
references
References 10 publications
0
5
0
Order By: Relevance
“…The basic results of this study are shown in Table 1 [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The data presented are summarized according to the comparative data on the photoinduced changes of the refractive index, Δ n i , for the model conjugated PI-based structure sensitized by the various nanoobjects.…”
Section: Resultsmentioning
confidence: 99%
“…The basic results of this study are shown in Table 1 [ 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 ]. The data presented are summarized according to the comparative data on the photoinduced changes of the refractive index, Δ n i , for the model conjugated PI-based structure sensitized by the various nanoobjects.…”
Section: Resultsmentioning
confidence: 99%
“…From the laser-induced changes of the refractive index, the nonlinear refraction n 2 and the third order susceptibility χ (3) were determined via procedure shown in the paper [11,14]. They were, respectively: ~10 -7 cm 2 kW -1 and ~10 -9 esu for thin conjugated films of the nanoobjects-doped organic structures; ~10 -6 cm 2 kW -1 and ~10 -8 esu for thin films of the nanoobjects-doped polymer-dispersed liquid crystals.…”
Section: Resultsmentioning
confidence: 99%
“…16. As new aspect of this study the nanoobjects structurization of inorganic systems has been found for polyvinyl alcohol (PVA) iodine films used as polarizators in display and telecommunications schemes.…”
Section: Surface Propertiesmentioning
confidence: 96%